Building a New Church : A Process Manual for Pastors and Lay Leaders - Healy, James E. (Book collections on Project MUSE., 2009)
The task of building a new worship space for a community is both overwhelming and sacred. It is a time of change that presents the opportunity for enrichment and catechesis. Using his experience of working with a steering committee to build a new church, Father James Healy in this volume takes a daunting task and makes it manageable. He provides engaging ideas for involving the parish community in decision making and for ensuring that the process of building a new church is a prayerful and sacred time. The result, as Healy notes, can bring surprising and fruitful rewards: 'The paradox I experienced was that I had set out to have the parish build their church, and in following all these processes, the new church built the parish.'